5’UTR gene regions in germline DNA sequencing panels: lessons from the analysis of breast and ovarian cancer patients of Tatar and Bashkir ethnic origin - Sokolenko, Anna P.; Venina, Aigul R.; Romanko, Alexandr A.; Belogubova, Evgenia V.; Sultanbayev, Alexandr V.; Askarov, Vadim E.; Mukhamediarova, Gulnara K.; Bakaeva, Elvina Kh; Syomina, Maria V.; Velyukhova, Tatiana Yu; Preobrazhenskaya, Elena V.; Togo, Alexandr V.; et al. (Familial cancer, 2025)
Background Tatars and Bashkirs are large and closely related ethnic communities that reside in the territory of the Russian Federation but have managed to preserve their national identity through the course of history. Methods This study included 446 Tatars, 53 Bashkirs, and 26 women of mixed Tatar-Bashkir ethnicity. Germline DNA analysis was performed for 349 breast cancer (BC) patients with clinical features of hereditary disease (family history, or young onset (</= 50 years), or BC bilaterality, or triple-negative receptor status (lack of expression of ER, PgR, and HER2) and 176 subjects with high-grade serous ovarian cancer (HGSOC). Results BRCA1 pathogenic variants (PVs) were detected in 63 women; surprisingly, five Slavic founder alleles accounted for 30 (48%) of the BRCA1 PVs. The genuine Tatar BRCA1 allele, c.5161C > T, was observed in 11 subjects. Among 27 women with BRCA2 PVs, six and five women were carriers of the c.-39-1_-39del and c.468dup variants, respectively. The loss-of-heterozygosity (LOH) test confirmed the pathogenic nature of the c.-39-1_-39del [rs758732038] allele, which is located in the 5’UTR of BRCA2 . Analysis of other BC-associated genes revealed single instances of PVs affecting PALB2 , TP53 , ATM , RAD51 , and RAD51D genes. Conclusion Tatars and Bashkirs, which are ethnically and religiously separated from Russians, carry an unexpectedly high proportion of Slavic BRCA1/2 founder alleles. The identification of recurrent Tatar/Bashkir BRCA2 pathogenic 5’UTR variant c.-39-1_-39del calls for a systematic analysis of regulatory regions of cancer-predisposing genes in patients with missing heritability.